Genetic Stock Identification and Adaptability of Hatchery-Reared Black Rockfish, Sebastes schlegelii, Released Into the North Yellow Sea waters - Liu, Qi; Wang, Ziwei; Li, Weiyuan; Zhang, Qi; Liu, Binwei; Li, Meiyuan; Liu, Ying; Tian, Tao; Yan, Hongwei (Frontiers in Marine Science, 2022)
Successful stock enhancement refers to the maintenance of economic profit, whilst minimizing negative genetic and ecological effects. As hatchery environments differ from natural habitats, post-release identification of hatchery-reared juveniles, and estimation of their adaptability are essential steps in conducting responsible stock enhancement. The black rockfish is an important fishery species in Japan, South Korea and China. Overfishing has dramatically decreased natural resources and a stock enhancement program was first initiated in the Liaodong peninsula in 2019. We traced this program and used nine microsatellite markers to identify 279 individuals as being hatchery-reared, out of 710 captured fish, with a resource contribution rate of 39.30%. These results indicated that stock enhancement of this species is likely to maintain a positive economic performance. To understand the potential genetic impacts on the local wild population, the genetic patterns of S. schlegelii stocks (wild controls from 2017, wild controls from 2018, female broodstock from 2019, recaptured hatchery-reared fish from 2019 and recaptured non-hatchery-reared fish from 2019 stocks) from the same habitat were evaluated before and after artificial stocking. We found that the S. schlegelii population was able to maintain high genetic diversity and showed weak genetic differentiation, but potential genetic introgression derived from stock enhancement should be concerned. The hatchery-reared individuals showed good adaptability, as shown by feeding condition and growth status. There was no obvious morphology difference between hatchery-reared fish and their wild counterparts, but hatchery-reared fish seemed to be bigger in size (significantly higher in MDB and BW), had a larger head (significantly larger in PRL/HL and ID/HL) and smaller paired fins (significantly smaller PCFL/BL), when compared with wild individuals across all investigation months. Our results provided insights into management of black rockfish enhancement in the future.